Clinical update on frontotemporal dementia: diagnosis and treatment. (October 2015) - Mocellin, Ramon; Scholes, Amelia; Walterfang, Mark; Looi, Jeffrey CL; Velakoulis, Dennis
Objectives: To provide a clinical update for general psychiatrists on frontotemporal dementias (FTDs) using a selective narrative review of recent findings and advances in conceptualising, diagnosing and treating FTD. Conclusions: General psychiatrists can apply their skills to support patients, carers, GPs and allied health workers in comprehensive care of persons with FTD.